A History of Islamic Philosophy, 3d ed.: By Majid Fakhry (New York: Columbia University Press, 2004. 430 pages.) (American Journal of Islam and Society, 2006)
That Majid Fakhry’s A History of Islamic Philosophy, first published in1970, has been brought out in a third revised edition can be of no surprise tothe many admirers of this most robust of scholars. Fakhry’s scholarship ismeticulous, and his style, even when handling the most complex ideas,remains simple and straightforward.As many of the theological questions raised by Islam’s key philosophers,particularly those pertaining to free will, justice, rights, and responsibilities,had political implications, each chapter in this book begins with ahistorical context. However, Fakhry only allows this context to play a subsidiaryrole, as a backdrop to the main narrative: the history of ideas. Thisapproach lends itself very well to an examination of the ideas held by bothindividual philosophers and schools of philosophy. Importantly, Fakhrydemonstrates how, during several key Islamic epochs, there was no onedominant system of thought, but rather, contending systems of thought. Hetakes us through these debates step by step, as in, for example, the first theologicalcontroversy on free will and predestination (qadar). It is in the presentationof these debates, more than anywhere else, that we see that while AHistory of Islamic Philosophy is distinguished from the work of many othergrand narrative histories by not being marred by a partisan viewpoint,Fakhry’s is by no means a clinically scientific approach.This book comprises thirteen chapters. It begins with “The Legacy ofGreece, Alexandria, and the Orient,” covers the watershed periods in the ...